2017
DOI: 10.1055/s-0036-1597923
|View full text |Cite
|
Sign up to set email alerts
|

Volar Plate Fixation in Patients Older Than 70 Years with AO Type C Distal Radial Fractures: Clinical and Radiologic Outcomes

Abstract: Treatment of unstable distal radial fractures (DRFs) in elderly patients is controversial, and considering the increasing life expectancy, their appropriate treatment is of growing importance. Our aim was to analyze the clinical and radiologic outcomes in the elderly patients with AO type C DRF treated with volar locking plate (VLP). Between 2007 and 2011, 572 DRFs were operated on in our hospital with open reduction and internal fixation with VLP. Of these, only 64 patients (66 DRFs) met the selection criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…To our knowledge, there are only 8 published reports of 24-month or longer outcomes in older populations, and, of those, only 2 reported intermediate time points. [8][9][10][11][12][13][14]16 Furthermore, no study conducted a concurrent comparison of all 4 currently accepted treatments. Arora et al 8 found no changes in radiographic alignment between 12-week and 4-year assessments of patients aged 70 years and older treated with casting or open reduction and internal fixation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, there are only 8 published reports of 24-month or longer outcomes in older populations, and, of those, only 2 reported intermediate time points. [8][9][10][11][12][13][14]16 Furthermore, no study conducted a concurrent comparison of all 4 currently accepted treatments. Arora et al 8 found no changes in radiographic alignment between 12-week and 4-year assessments of patients aged 70 years and older treated with casting or open reduction and internal fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies followed older adults longer than 12 months, and those that did only reported results from the final assessment; intermediate outcomes to track the trajectory of recovery were missing. [8][9][10][11][12][13][14][15][16] Long-term outcomes on injuries in older adults are especially germane because today's older generation is living longer and leading more active lives than previous generations. In this era of value-based care and shared decision-making, long-term outcomes help to guide surgeons, patients, and their families through understanding the benefits and risks of each treatment.…”
Section: Introductionmentioning
confidence: 99%